Preschool teachers' knowledge on dyslexia: a Malaysian experience - Ramli, Shalinawati; Idris, Idayu Badilla; Omar, Khairani; Harun, Dzalani; Surat, Shahlan; Mohamad Yusop, Yusni; Zainudin, Zaida Nor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Teachers play a vital role in identifying students with dyslexia. The acquisition of this knowledge will help teachers to classify students who are at risk of dyslexia. The objective of this study is to identify the level of teachers’ knowledge about dyslexia that comprises of its general knowledge, diagnosis, symptoms and treatments. A cross sectional study was done upon 138 preschool teachers. This research was conducted by using ‘Knowledge and Beliefs about Developmental Dyslexia’ questionnaire, which consists of 36 items with 3 Likert scale questions. Findings revealed that the level of general knowledge possessed by the pre-school teachers was relatively different based on the construct even though they have respectively received the Diploma in Early Childhood Education. On the same hand, most of the respondents were found to be having higher understanding on the general knowledge about dyslexia compared to their understanding on the symptoms, diagnosis and the treatments.